2013
DOI: 10.15388/na.18.4.13969
|View full text |Cite
|
Sign up to set email alerts
|

Pulsating flow of an incompressible micropolar fluid between permeable beds

Abstract: The paper deals with the pulsating flow of an incompressible micropolar fluid through a channel bounded by permeable beds. The fluid is injected into the channel from the lower permeable bed with a certain velocity and is sucked into the upper permeable bed with the same velocity. The flow between the permeable beds is assumed to be governed by micropolar fluid flow equations and that in the permeable regions by Darcy law. The Beavers–Joseph (BJ) slip boundary conditions are used at the interfaces of the perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Nowadays, a micropolar non-Newtonian model has been gradually arrayed in several sections on medical-related fields and imperative applications in pharmaceutical, food industries, chemical engineering, heat, and mass transmission (9)(10)(11). The micropolar (non-Newtonian) fluid is categorized by microstructures, rigid and arbitrarily absorbed particles the fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a micropolar non-Newtonian model has been gradually arrayed in several sections on medical-related fields and imperative applications in pharmaceutical, food industries, chemical engineering, heat, and mass transmission (9)(10)(11). The micropolar (non-Newtonian) fluid is categorized by microstructures, rigid and arbitrarily absorbed particles the fluid flow.…”
Section: Introductionmentioning
confidence: 99%
“…Eringen [21] formulated a much complex structure for simulating effective micro-rheological properties and areas of applications in various industrial and engineering fields like chemical engineering, synovial fluid, biofluids, semi-circular canal fluids, gastric liquids, and slurry technologies. Presently, a micropolar paradigm has been progressively deployed in various wings in the medical fields [22][23][24][25][26]. Nasir et al [27] discussed the MHD radiative flow nanofluid with SWCNTs through a revolving stretchable disk with velocity slip effects.…”
Section: Introductionmentioning
confidence: 99%
“…Fan and Chao calculated the excess power dissipated due to harmonic motion superimposed on a steady flow and observed that the excess power decreases with an increase in oscillatory frequency. Recently pulsatile flow has also been evaluated for enhanced cleaning of fouling layers, micropolar and non-Newtonian fluid flow between permeable beds, , and separation of species . Qi et al have modeled pulsatile flow in rectangular channels with application toward cleaning of microfluidic devices.…”
Section: Introductionmentioning
confidence: 99%